A high wear-resistant phenolic resin for sandpaper and its preparation process
By adding isocyanate polyarylethersulfone polymer to the phenolic resin and performing curing cross-linking reaction, the problem of insufficient wear resistance and strength of the phenolic resin for sandpaper is solved, and higher wear resistance and water resistance are achieved.
Patent Information
- Application Number
- CN202411147611.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-20
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-08-20
AI Technical Summary
The phenolic resin used for sandpaper has low wear resistance and low strength, making it difficult to meet the performance requirements of sandpaper in surface grinding of metals, woods, etc.
By adding isocyanate polyarylethersulfone polymer to the phenolic resin, the isocyanate group in its side chain and the hydroxyl group of the phenolic resin undergoes curing cross-linking reaction, thereby enhancing the interface bonding strength between the polyarylethersulfone and the phenolic resin, and forming a tight Cross-linking network.
It significantly improves the tensile strength and elongation of the cured substance, reduces the amount of friction and wear, improves wear and water resistance, and makes phenolic resin more widely used in sandpaper.
Smart Images

Figure CN118879020B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of phenolic resins, in particular to a high-wear-resistant phenolic resin for sandpaper and a preparation process thereof. Background Art
[0002] Sandpaper is widely used in surface grinding of metal, wood and other materials. It is required to have good wear resistance, water resistance and strength. Sandpaper is mainly composed of base paper, abrasive and adhesive. The adhesive plays a decisive role in the wear resistance and water resistance of sandpaper. Phenolic resin has good bonding performance, high temperature resistance and good chemical resistance. It can be used as an adhesive and is widely used in sandpaper, wooden furniture, construction materials and other fields. Improving the mechanical strength, wear resistance and water resistance of phenolic resin adhesive can make phenolic resin have better practical application in sandpaper.
[0003] Polyarylethersulfone polymers have the advantages of good toughness, high strength, high temperature resistance, good wear resistance, etc., and have broad application prospects in adhesives, coatings and other materials. Patent CN113214443B discloses a stearic acid-modified polysulfone phenolic resin and its preparation method and application in the preparation of tire rubber. By introducing linoleic acid into the chemical structure of polysulfone for modification, the phenolic resin can have excellent hardness and impact strength, flexibility and anti-aging properties. However, the stearic acid-modified polysulfone of the patent does not improve the water resistance and wear resistance of the phenolic resin, which is not conducive to the practical application of the phenolic resin in the adhesive for sandpaper. Summary of the invention
[0004] The invention solves the problem that the phenolic resin used for sandpaper has low wear resistance and low strength.
[0005] The technical scheme of the invention is: a highly wear-resistant phenolic resin for sandpaper, comprising 100 parts by weight of phenolic resin and 3-30 parts by weight of isocyanate polyarylethersulfone polymer.
[0006] The preparation reaction of isocyanate polyarylethersulfone polymer is:
[0007] Step (1), adding toluene, 4,4-dichlorodiphenyl sulfone in a molar ratio of (75-90):(10-25):100:(200-240), acrylate-based benzimide dichloro monomer, hydroquinone, and potassium carbonate to sulfolane, heating to 130-140° C. to azeotropically remove water for 3-4 hours, then heating to 190-200° C., reacting for 5-8 hours, cooling and adding dilute hydrochloric acid solution, filtering and placing the precipitate in distilled water, heating to boiling, stirring and filtering, washing with ethanol, and drying to obtain an acrylate-based polyarylethersulfone polymer.
[0008] The acrylated benzimide dichloride monomer has the structural formula (I) shown below.
[0009]
[0010] Step (2), adding an acrylate-based polyarylethersulfone polymer to N,N-dimethylformamide, stirring to dissolve, and then adding styrene, 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate, and an initiator in a nitrogen atmosphere, stirring to carry out a polymerization reaction, heating acetone to precipitate a precipitate, filtering, washing with xylene, and drying to obtain an isocyanate polyarylethersulfone polymer.
[0011] Preferably, in step (2), the mass ratio of acrylate-based polyarylethersulfone polymer, styrene, 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate, and initiator is 100:(2-8):(1.2-6):(0.024-0.11).
[0012] Preferably, the initiator is dicumyl peroxide or azobisisobutyronitrile.
[0013] Preferably, in step (2), the polymerization reaction temperature is 70-90° C. and the time is 7-10 h.
[0014] Preferably, the preparation process of acrylate-based benzimide dichloride monomer is:
[0015] Step A, adding 4,4'-biphenyl ether dianhydride and 3-amino-5-chlorophenol in a molar ratio of 1:(1.9-2.1) to N,N-dimethylformamide, diluting with water after the reaction, then extracting with dichloromethane, drying the organic phase to remove water, distilling under reduced pressure, and recrystallizing the precipitate in ethanol to obtain hydroxybenzene imide dichloro monomer.
[0016] Step B: In an ice bath, add hydroxybenzamide dichloride monomer, acryloyl chloride, and triethylamine in a molar ratio of 1:(2-2.4):(2-2.4) to dichloromethane, react at 20-30° C. for 6-10 hours, distill under reduced pressure, wash the precipitate with water, and then recrystallize from ethanol to obtain acrylated benzamide dichloride monomer.
[0017] Preferably, in step A, the reaction is first carried out at 20-30° C. for 2-3 h, and then at 140-145° C. for 10-15 h.
[0018] Preferably, the preparation process of the highly wear-resistant phenolic resin for sandpaper is characterized in that the preparation process comprises adding phenolic resin and isocyanate polyarylethersulfone polymer into toluene, stirring and mixing, and obtaining the highly wear-resistant phenolic resin for sandpaper.
[0019] The present invention has the following technical effects: the present invention uses acrylate-based benzimide dichloro monomer as a functional monomer, and carries out polycondensation reaction with 4,4-dichlorodiphenyl sulfone and hydroquinone to obtain an acrylate-based polyarylethersulfone polymer containing alkenyl groups in the side chain. Then, under the action of an initiator such as azobisisobutyronitrile, a graft polymerization reaction is carried out with styrene and 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate to obtain an isocyanate polyarylethersulfone polymer, thereby introducing a polystyrene polymer containing an isocyanate group into the side chain of the polyarylethersulfone polymer.
[0020] The present invention adds isocyanate polyarylethersulfone polymer to phenolic resin, and the isocyanate group of the side chain thereof undergoes curing and crosslinking reaction with the hydroxyl group of the phenolic resin, thereby enhancing the interface bonding strength between the polyarylethersulfone polymer and the phenolic resin. The polyarylethersulfone has the advantages of high toughness and high strength, and at the same time, the main chain of the molecule contains a rigid aromatic imide ring structure, which has high strength and high wear resistance, so that after the polyarylethersulfone and the phenolic resin are cured, the tensile strength and elongation at break of the cured product are significantly improved, the friction and wear amount are reduced, and the wear resistance is improved.
[0021] The isocyanate polyarylethersulfone polymer of the present invention undergoes a curing crosslinking reaction with the hydroxyl group of the phenolic resin to form a compact crosslinking network in the phenolic resin matrix, thereby increasing the crosslinking degree of the molecular chains of the phenolic resin and preventing water molecules from entering the cured matrix, thereby reducing the water absorption rate of the cured product and improving water resistance. The present invention has good practical application in adhesives for sandpaper. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is the reaction formula for preparing acrylate-based benzimide dichloride monomer.
[0023] Figure 2 It is the reaction formula for preparing acrylate-based polyarylethersulfone polymer.
[0024] Figure 3 It is the reaction formula for preparing isocyanate polyarylethersulfone polymer. DETAILED DESCRIPTION
[0025] In order to make the purpose, technical solution and advantages of the present disclosure clearer, the technical solution of the present disclosure will be clearly and completely described in combination with the embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, not all of the embodiments. Based on the embodiments in the present disclosure, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present disclosure. It should be noted that the embodiments in the present disclosure and the features in the embodiments can be arbitrarily combined with each other without conflict.
[0026] Example 1
[0027] (1) Add 6 mmol 4,4'-biphenyl ether dianhydride and 12.6 mmol 3-amino-5-chlorophenol (CAS registration number 883195-40-2) to 15 mL N,N-dimethylformamide, react at 25°C for 2 hours, then at 145°C for 10 hours, dilute with water, extract with dichloromethane, dry the organic phase to remove water, distill under reduced pressure, and recrystallize the precipitate in ethanol to obtain hydroxybenzene imide dichloro monomer.
[0028] (2) In an ice bath, add 5 mmol of hydroxybenzamide dichloride monomer, 10 mmol of acryloyl chloride, and 10 mmol of triethylamine to 30 mL of dichloromethane, react at 20°C for 8 h, distill under reduced pressure, wash the precipitate with water, and then recrystallize from ethanol to obtain acrylated hydroxybenzamide dichloride monomer.
[0029] (3) Add 25 mL of toluene, 9 mmol of 4,4-dichlorodiphenyl sulfone, 1 mmol of acrylated benzimide dichloro monomer, 10 mmol of hydroquinone, and 24 mmol of potassium carbonate to 80 mL of cyclopentane sulfone, heat to 130°C for azeotropic dehydration for 4 hours, then raise the temperature to 200°C and react for 5 hours. After cooling, add dilute hydrochloric acid solution, filter and place the precipitate in distilled water, heat to boiling, filter after stirring, wash with ethanol, and dry to obtain an acrylated polyarylethersulfone polymer.
[0030] (4) Add 20 g of acrylate polyarylethersulfone polymer to 300 mL of N,N-dimethylformamide, stir to dissolve, then add 0.4 g of styrene, 0.24 g of 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate (CAS registration number 2094-99-7), and 4.8 mg of azobisisobutyronitrile as initiator in a nitrogen atmosphere, heat to 90° C., stir to carry out polymerization reaction for 7 h, heat acetone to precipitate the precipitate, filter, wash with xylene, and dry to obtain isocyanate polyarylethersulfone polymer.
[0031] (5) Add 100 g of phenolic resin and 3 g of isocyanate polyarylethersulfone polymer to 250 mL of toluene, stir and mix well to obtain a highly wear-resistant phenolic resin for sandpaper.
[0032] Example 2
[0033] (1) Add 6 mmol 4,4'-biphenyl ether dianhydride and 11.4 mmol 3-amino-5-chlorophenol to 15 mL N,N-dimethylformamide, react at 20°C for 3 h, then at 140°C for 15 h, dilute with water, extract with dichloromethane, dry the organic phase to remove water, distill under reduced pressure, and recrystallize the precipitate in ethanol to obtain hydroxybenzene imide dichloro monomer.
[0034] (2) In an ice bath, add 5 mmol of hydroxybenzamide dichloride monomer, 12 mmol of acryloyl chloride, and 12 mmol of triethylamine to 30 mL of dichloromethane, react at 20°C for 10 h, distill under reduced pressure, wash the precipitate with water, and then recrystallize from ethanol to obtain acrylated hydroxybenzamide dichloride monomer.
[0035] (3) Add 35 mL of toluene, 8.2 mmol of 4,4-dichlorodiphenyl sulfone, 1.8 mmol of acrylated benzimide dichloro monomer, 10 mmol of hydroquinone, and 20 mmol of potassium carbonate to 100 mL of cyclopentane sulfone, heat to 140°C to remove water by azeotropic reaction for 3 hours, then raise the temperature to 190°C and react for 8 hours. After cooling, add dilute hydrochloric acid solution, filter and place the precipitate in distilled water, heat to boiling, filter after stirring, wash with ethanol, and dry to obtain an acrylated polyarylethersulfone polymer.
[0036] (4) Add 20 g of acrylate polyarylethersulfone polymer to 300 mL of N,N-dimethylformamide, stir to dissolve, then add 1 g of styrene, 0.7 g of 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate, and 15 mg of azobisisobutyronitrile as initiator in a nitrogen atmosphere, heat to 70°C, stir to carry out polymerization reaction for 8 h, heat acetone to precipitate the precipitate, filter, wash with xylene, and dry to obtain isocyanate polyarylethersulfone polymer.
[0037] (5) Add 100 g of phenolic resin and 3 g of isocyanate polyarylethersulfone polymer to 250 mL of toluene, stir and mix well to obtain a highly wear-resistant phenolic resin for sandpaper.
[0038] Example 3
[0039] (1) Add 6 mmol 4,4'-biphenyl ether dianhydride and 12 mmol 3-amino-5-chlorophenol to 20 mL N,N-dimethylformamide, react at 30°C for 2 hours, then at 140°C for 15 hours, dilute with water, extract with dichloromethane, dry the organic phase to remove water, distill under reduced pressure, and recrystallize the precipitate in ethanol to obtain hydroxybenzene imide dichloro monomer.
[0040] (2) In an ice bath, add 5 mmol of hydroxybenzamide dichloride monomer, 10 mmol of acryloyl chloride, and 10 mmol of triethylamine to 30 mL of dichloromethane, react at 30°C for 6 h, distill under reduced pressure, wash the precipitate with water, and then recrystallize from ethanol to obtain acrylated hydroxybenzamide dichloride monomer.
[0041] (3) Add 25 mL of toluene, 7.5 mmol of 4,4-dichlorodiphenyl sulfone, 2.5 mmol of acrylated benzimide dichloro monomer, 10 mmol of hydroquinone, and 24 mmol of potassium carbonate to 80 mL of cyclopentane sulfone, heat to 130°C to remove water by azeotropic method for 4 hours, then raise the temperature to 190°C and react for 8 hours. After cooling, add dilute hydrochloric acid solution, filter and place the precipitate in distilled water, heat to boiling, filter after stirring, wash with ethanol, and dry to obtain acrylated polyarylethersulfone polymer.
[0042] (4) Add 20 g of acrylate polyarylethersulfone polymer to 300 mL of N,N-dimethylformamide, stir to dissolve, then add 1.6 g of styrene, 1.2 g of 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate, and 22 mg of diisopropylbenzene peroxide as an initiator in a nitrogen atmosphere, heat to 70° C., stir to carry out polymerization reaction for 10 h, heat acetone to precipitate the precipitate, filter, wash with xylene, and dry to obtain isocyanate polyarylethersulfone polymer.
[0043] (5) Add 100 g of phenolic resin and 3 g of isocyanate polyarylethersulfone polymer to 250 mL of toluene, stir and mix well to obtain a highly wear-resistant phenolic resin for sandpaper.
[0044] Comparative Example 1
[0045] The difference between this comparative example and Example 1 is that no isocyanate polyarylethersulfone polymer is added to the phenolic resin.
[0046] (1) Add 100 g of phenolic resin to 250 mL of toluene and stir to mix well to obtain a high wear-resistant phenolic resin for sandpaper.
[0047] Comparative Example 2
[0048] The difference between this comparative example and Example 1 is that 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate is not added when preparing the polyarylethersulfone polymer.
[0049] (1) Add 20 g of acrylate-based polyarylethersulfone polymer to 300 mL of N,N-dimethylformamide, stir to dissolve, then add 0.4 g of styrene and 4.8 mg of azobisisobutyronitrile as initiator in a nitrogen atmosphere, heat to 90° C., stir to carry out polymerization reaction for 7 h, heat acetone to precipitate the precipitate, filter, wash with xylene, and dry to obtain a polyarylethersulfone polymer.
[0050] (2) Add 100 g of phenolic resin and 3 g of polyarylethersulfone polymer to 250 mL of toluene, stir and mix well to obtain a high wear-resistant phenolic resin for sandpaper.
[0051] Comparative Example 3
[0052] The difference between this comparative example and Example 1 is that no acrylated benzimide dichloride monomer is added when preparing the polyarylethersulfone polymer.
[0053] (1) Add 25 mL of toluene, 10 mmol of 4,4-dichlorodiphenyl sulfone, 10 mmol of hydroquinone, and 24 mmol of potassium carbonate to 80 mL of cyclopentane sulfone, heat to 130°C for azeotropic dehydration for 4 hours, then raise the temperature to 200°C, react for 5 hours, cool, add dilute hydrochloric acid solution, filter, place the precipitate in distilled water, heat to boiling, stir, filter, wash with ethanol, and dry to obtain a polyarylethersulfone polymer.
[0054] (2) Add 100 g of phenolic resin and 3 g of polyarylethersulfone polymer to 250 mL of toluene, stir and mix well to obtain a high wear-resistant phenolic resin for sandpaper.
[0055] The wear-resistant phenolic resin is cast into a mold, vacuum degassed, placed in an oven, first heat-cured at 80°C for 5 hours, and then cured at 140°C for 2 hours to prepare a phenolic resin cured product.
[0056] The phenolic resin cured product is made into a 10cm×10cm×0.4cm sample, weighed, recorded as m0, then immersed in water for 24 hours, the film is taken out, the surface moisture is wiped off, weighed, recorded as m1; the water absorption rate W is calculated. W=(m1-m0) / m0×100%.
[0057] The tensile properties of phenolic resin cured products were tested using a universal testing machine according to the method of GB / T 2567-2021.
[0058] The friction and wear performance of phenolic resin cured product was tested by a wear tester. The friction pair was 45# steel, the load value was 200N, the speed was 300r / min, and the wear time was 30h. The mass before and after wear was weighed, and the wear amount △m was calculated, △m=M1-M0.
[0059] Table 1 Performance test of phenolic resin cured product
[0060]
[0061] As can be seen from Table 1, compared with Comparative Example 1, isocyanate polyarylethersulfone polymers are added to the phenolic resins of Examples 1, 2, and 3, and the isocyanate groups of the side chains undergo a curing and cross-linking reaction with the hydroxyl groups of the phenolic resin, thereby enhancing the interfacial bonding strength between the polyarylethersulfone polymer and the phenolic resin. The polyarylethersulfone has the advantages of high toughness and high strength. At the same time, the main chain of the molecule contains a rigid aromatic imide ring structure, which has high strength and high wear resistance. After the polyarylethersulfone and the phenolic resin are cured, the tensile strength and elongation at break of the cured product are significantly improved, the friction and wear amount are reduced, and the wear resistance is improved.
[0062] The isocyanate polyarylethersulfone polymer undergoes a curing and cross-linking reaction with the hydroxyl group of the phenolic resin to form a tight cross-linking network in the phenolic resin matrix, thereby increasing the cross-linking degree of the molecular chain of the phenolic resin and preventing water molecules from entering the cured matrix, thereby reducing the water absorption rate of the cured product and improving water resistance.
[0063] In Comparative Example 2, 3-isopropenyl-a,a'-dimethylbenzyl isocyanate is not added during the preparation of the polyaryl ether sulfone polymer. The obtained polyaryl ether sulfone polymer does not contain isocyanate groups and cannot undergo a curing and cross-linking reaction with the phenolic resin, resulting in poor compatibility of the polyaryl ether sulfone polymer with the phenolic resin, inability to effectively improve the tensile properties and wear resistance of the phenolic resin, and a high water absorption rate.
[0064] In Comparative Example 3, when preparing the polyarylethersulfone polymer, no acrylate-based phenylimide dichloride monomer is added, and the obtained polyarylethersulfone polymer does not contain a rigid aryl imide ring structure. At the same time, the polyarylethersulfone polymer does not contain an olefin group, and cannot undergo polymerization reaction with styrene and 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate. The polyarylethersulfone polymer does not contain an isocyanate group and cannot undergo a curing and cross-linking reaction with the phenolic resin. The compatibility between the two is poor, and the tensile properties and wear resistance of the phenolic resin cannot be effectively improved, and the water absorption rate is relatively large.
[0065] Taking Example 1 as an example, the amount of isocyanate poly(arylethersulfone) polymer (PSF) is controlled to be 5-30 g.
[0066] Table 2 Performance test of wear-resistant phenolic resin
[0067]
[0068] It can be seen from Table 2 that with the gradual increase in the amount of isocyanate polyarylethersulfone polymer, the wear-resistant phenolic resin has good tensile strength and elongation at break, as well as lower water absorption and wear, showing good mechanical properties, wear resistance and water resistance.
[0069] The above embodiments are only used to illustrate the technical solutions of the present disclosure, rather than to limit them. Although the present disclosure is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present disclosure.
Claims
1. A highly wear-resistant phenolic resin for sandpaper, characterized in that: The highly wear-resistant phenolic resin for sandpaper comprises 100 parts by weight of phenolic resin and 3-30 parts by weight of isocyanate polyarylethersulfone polymer; The preparation reaction of the isocyanate polyarylethersulfone polymer is: Step (1), adding toluene, 4,4-dichlorodiphenyl sulfone, acrylated benzimide dichloro monomer, hydroquinone, and potassium carbonate to sulfolane, heating to 130-140° C. to remove water by azeotropy for 3-4 hours, then heating to 190-200° C., reacting for 5-8 hours, cooling, adding dilute hydrochloric acid solution, filtering, placing the precipitate in distilled water, heating to boiling, stirring, filtering, washing, and drying to obtain an acrylated polyarylethersulfone polymer; The acrylated benzimide dichloride monomer has the structural formula (I) as follows: Step (2), adding an acrylate-based polyarylethersulfone polymer to N,N-dimethylformamide, stirring to dissolve, and then adding styrene, 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate, and an initiator in a nitrogen atmosphere, stirring to carry out a polymerization reaction, heating acetone to precipitate a precipitate, filtering, washing with xylene, and drying to obtain an isocyanate polyarylethersulfone polymer; The preparation process of the acrylate-based benzimide dichloride monomer is as follows: Step A, adding 4,4'-biphenyl ether dianhydride and 3-amino-5-chlorophenol to N,N-dimethylformamide, diluting with water after the reaction, extracting, and recrystallizing to obtain hydroxybenzene imide dichloro monomer; Step B, in an ice bath, add hydroxybenzamide dichloride monomer, acryloyl chloride, and triethylamine to dichloromethane at 20-30° C. for 6-10 hours, perform vacuum distillation, wash, and recrystallize to obtain acrylated benzamide dichloride monomer; In the step A, the molar ratio of 4,4'-biphenyl ether dianhydride to 3-amino-5-chlorophenol is 1:(1.9-2.1); In the step B, the molar ratio of hydroxybenzene imide dichloride monomer, acryloyl chloride and triethylamine is 1:(2-2.4):(2-2.4).
2. The highly wear-resistant phenolic resin for sandpaper according to claim 1, characterized in that: In the step (1), the molar ratio of 4,4-dichlorodiphenyl sulfone, acrylate-based benzimide dichloro monomer, hydroquinone, and potassium carbonate is (75-90):(10-25):100:(200-240).
3. The highly wear-resistant phenolic resin for sandpaper according to claim 1, characterized in that: In the step (2), the mass ratio of acrylate-based polyarylethersulfone polymer, styrene, 3-isopropenyl-a,a'-dimethylbenzyl-isocyanate, and initiator is 100:(2-8):(1.2-6):(0.024-0.11).
4. The highly wear-resistant phenolic resin for sandpaper according to claim 3, characterized in that: The initiator is dicumyl peroxide or azobisisobutyronitrile.
5. The highly wear-resistant phenolic resin for sandpaper according to claim 1, characterized in that: In the step (2), the polymerization reaction temperature is 70-90° C. and the time is 7-10 hours.
6. The highly wear-resistant phenolic resin for sandpaper according to claim 1, characterized in that: In the step A, the reaction is first carried out at 20-30° C. for 2-3 h, and then at 140-145° C. for 10-15 h.
7. A process for preparing a highly wear-resistant phenolic resin for sandpaper according to any one of claims 1 to 6, characterized in that: The preparation process comprises the following steps: adding phenolic resin and isocyanate polyarylethersulfone polymer into toluene, stirring and mixing, and obtaining high-wear-resistant phenolic resin for sandpaper.
Citation Information
Patent Citations
A stearyl acylated polysulfone modified phenolic resin, its preparation method, and its application in the preparation of tire rubber.
CN113214443B
Phenolic aldehyde-based regenerable polymer material as well as preparation method and regeneration application thereof
CN111333807A
Modified phenol resins
US20110060105A1